2007
DOI: 10.4028/www.scientific.net/msf.546-549.1501
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Mechanical Properties of C/C-SiC Composites

Abstract: Porous C/C composite with certain porosity prepared by Chemical vapor infiltration (CVI) was chosen as the preforms to develop the C/C-SiC composites through precursor infiltration and pyrolysis(PIP), using PCS (polycarbosilane) as the precursor and divinylbenzene as solvent and cross-linking reagent for PCS. The effect of the infiltration solution with different PCS/DVB ratio on the final density, microstructure, and mechanical properties of composites was investigated and the proper PCS/DVB ratio to prepare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…where k % 0.75 for a Berkovich indenter [27]. Again, the contact stiffness (S) which is the slope of the first $1/3rd linear part recorded during the unloading cycle of the load versus depth of penetration plot can be expressed as [28] S ¼ dP dh…”
Section: Basic Theory Of Nanoindentationmentioning
confidence: 99%
“…where k % 0.75 for a Berkovich indenter [27]. Again, the contact stiffness (S) which is the slope of the first $1/3rd linear part recorded during the unloading cycle of the load versus depth of penetration plot can be expressed as [28] S ¼ dP dh…”
Section: Basic Theory Of Nanoindentationmentioning
confidence: 99%
“…Previous studies demonstrated that the shear strength of SiC along the (100) direction declined as the decrease of Si/C ratio based on the first principles [12]. The experimental results manifested that the cleanliness of SiC grain boundaries declined with the decreased Si/C ratio due to the precipitation of free carbon [13]. Furthermore, the flexural strength of C/C-SiC composites also showed an increasing and then decreasing trend with the decreased Si/C ratio in SiC matrix [14].…”
Section: Introductionmentioning
confidence: 80%
“…3 The impurities on the surface of fiber were removed after the alkali treatment, and the surface became smooth after the fiber treated by silane coupling agent. 4 Subramanya et al 5 conducted the alkali treatment on banana fiber could remove impurities on the surface of banana fiber, and improve the interaction between fiber and cassava starch. Therefore, the surface property of sisal fiber could play an important role in the mechanical and thermal properties of polymer composite and need further research.…”
Section: Introductionmentioning
confidence: 99%